2010
DOI: 10.1080/07315724.2010.10719833
|View full text |Cite
|
Sign up to set email alerts
|

Almond Consumption and Cardiovascular Risk Factors in Adults with Prediabetes

Abstract: An ADA diet consisting of 20% of calories as almonds over a 16-week period is effective in improving markers of insulin sensitivity and yields clinically significant improvements in LDL-C in adults with prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
139
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(150 citation statements)
references
References 29 publications
8
139
2
1
Order By: Relevance
“…In addition, lipid abnormalities may mediate this effect; hyperlipidemia in obese hypertensive individuals has been attributed to impairment of the baroreceptor reflex leading to increased BP [34]. In pre-diabetes subjects with insulin resistance, no improvement of systolic BP was noted after almond consumption [16,35].. In the present study, systolic BP was decreased significantly in all intervention groups but not the control group who maintained their habitual diet and did not consume almonds.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In addition, lipid abnormalities may mediate this effect; hyperlipidemia in obese hypertensive individuals has been attributed to impairment of the baroreceptor reflex leading to increased BP [34]. In pre-diabetes subjects with insulin resistance, no improvement of systolic BP was noted after almond consumption [16,35].. In the present study, systolic BP was decreased significantly in all intervention groups but not the control group who maintained their habitual diet and did not consume almonds.…”
Section: Discussioncontrasting
confidence: 45%
“…However, dietary intervention with almonds has improved markers of insulin sensitivity in adults with prediabetes [16]. Independently, consumption of almonds was shown to influence a few but not all markers of inflammation and haemostasis in a dose-independent manner [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that a similar effect was achieved in the group consuming olive oil [20]. The consumption of almonds (56 g/d) was also associated with the reduction of the HOMA-IR index in patients by 40% and the decrease in insulin secretion by 24-33% [17][18][19]. It is concluded that nuts can be a positive factor in the glycaemic control and in the improvement of the insulin sensitivity and the effect was the most frequently observed after 4-6 weeks.…”
Section: Role Of Nuts In the Postprandial Glycaemia Control And An Inmentioning
confidence: 60%
“…The evidence submitted above confirmed, that nuts reveal positive impact on the glycaemic index and the tissue resistance [13][14][15][16][17][18][19]. However, in the process of disease progress monitoring there is an additional index applied -HbA 1c , which enables to reflect the glycaemic state up to three months back, which is linked to the period of the erythrocyte life cycle (8-12 weeks) [4,27].…”
Section: The Impact Of the Nut Consumption On The Glycaemic Indexmentioning
confidence: 93%
See 1 more Smart Citation